The influence of wind selectivity on migratory behavioral strategies. (20th October 2017) - McCabe, Jennifer D; Olsen, Brian J; Osti, Bipush; Koons, Peter O
Abstract : When preferred outcomes to a decision are unavailable, animals must decide when to settle. Migrating birds that are too picky about which winds to use may never reach their goal, but birds that are not picky enough may be blown off-course. By modeling North American migrants, we determined that birds on a tight time-schedule should be less picky, although pickier birds expend less energy while migrating more slowly. Our values match field calculations from Europe. Abstract: Air and water currents affect the timing and energy expenditure of many migratory animals, and therefore selection of favorable currents is important for optimal migratory performance. However, waiting for favorable currents also incurs costs. Here we conduct an optimality analysis to determine how wind selectivity affects 3 migratory currencies: time, energy, and risk. To describe variation in these metrics under varying degrees of selectivity, we constructed an individual-based model to simulate fall migration of passerines across eastern North America, allowing birds to use different thresholds of wind profit as the criterion for daily departure. A gradient of thresholds were tested across a range of realistic wind currents, from initiating flights only on nights when winds were directed in their preferred migratory direction (highly selective), to flying under most wind conditions (low selectivity). Our analysis indicated that relative mortality risk was lowest at intermediate selectivity; energy expended during flight was least for the most selective individuals; and of those that successfully completed migration, time spent on migration was lowest for the least selective birds. We solved for the optimal range of wind selectivity and show that this departure criterion alone can produce a tradeoff between time and energy that has been seen in many other behavioral contexts. While we solved for optima using some conditions specific to eastern North America, we show that variation in wind selectivity at departure can produce migratory behaviors that mimic the classic "time-minimizer" and "energy-minimizer" strategies developed from measurements of wild birds across multiple continents.